Pointers: The Missing Link between Intentionality and Reference. - Simons, Peter (Grazer Philosophische Studien, 2017)
Reference can fail in a way that intentionality cannot. Though the stream of phenomenal experience typically does not fail to target (be about, refer to) objects outside, it may do. How does the mind go about targeting objects beyond itself? The speculative conjecture of this paper is that it does so by a type of process which can be called pointing, and that the acts or act-aspects of pointing can be called pointers. The notion of a pointer has several suggestive roots. One is the familiar physical gesture of pointing. Another is the existence of directional signs such as on roads. The third is the software data types making direct reference to memory locations in computers, also called 'pointers'. A final source is demonstrative pronouns and other deictic expressions in language, of which Peter Geach wrote, "a demonstrative pronoun...works like a pointer, not like a label". I suggest that there is in the mental cognitive repertoire a structurally and semantically analogous type of act which pierces the passivity of perception, directs us outside the machine, and prepares the way for drawing others' minds to the same thing.